THE DEFENSE ECONOMICS APPROACH TO SYNCHRONIZING DEFENSE AND ECONOMIC DEVELOPMENT POLICIES IN INDONESIA - Kennedy, Posma Sariguna Johnson (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
This study aims to explain the latest phenomenon that economy and defense must be mutually aligned so that people's welfare increases. The main priority is not only improving the economy but also in providing adequate security and defense so that economic actors can carry out their economic activities optimally. The method used in this study is a qualitative study, which has a focus on how to get data and literature that has deep meaning. From this method, we want to get a relationship between the defense and the economic sectors so that both areas must be equally seen as necessary in the ideals of improving social welfare, with the realization that the development of defense and economic programs must go hand in hand.